Métodos de control postcosecha de antracnosis en frutas - Rubio Araujo, Fabio Nolberto (2015)
The aim of this review is to provide enough information to the producer, supplier, consumer, agricultural export companies and the scientific community in general. On more recent methods used in the control postharvest anthracnose in fruits, so that it can choose which type of control used to reduce fungal inoculum in the horticultural center. Anthracnose has been identified as the main limiting factor in plant pathology various types of fruits in the postharvest stage globally, causing losses from 40% to 100%, for this reason seek safer alternatives to synthetic fungicides which are effective and economically viable and environmentally friendly. One of these is biological control because it has been proven effective in minimizing the damage of this disease, this is characterized by using antagonistic microorganisms (bacteria, yeasts and fungi) these have the ability to exert an effect of biological control of different pathogens of interest. In recent years has been using a variety of antagonistic microorganisms (Bacillus subtilis, lichiniformis bacillus, munita Rhodotorula, etc.), which are being developed fungicides organic and safe way, which have multiple benefits compared with chemicals, because they generate resistance and do not accumulate chemical residues in fruits, also postulated that can be inoculant and growth stimulator on the other hand is using the physical, cultural and chemical control.